2020
DOI: 10.1002/lno.11475
|View full text |Cite
|
Sign up to set email alerts
|

Mud‐associated organic matter and its direct and indirect role in marsh organic matter accumulation and vertical accretion

Abstract: In situ plant production is often assumed to be the major contributor to organic matter (OM) accumulation and vertical accretion in tidal marshes. Here, we evaluate the contribution of mud-associated OM in salt and brackish marshes in Louisiana. Based on 14 soil cores, the OM content of the mud fraction-i.e., any material smaller than 64 μm-was 17% AE 7% for the salt marshes and 28% AE 14% for the brackish marshes. This remains nearly uniform over the top 35 cm depth, suggesting that this material is deposited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…In the inner marshes, organic deposition is more important, indicating that mineral sediment is less available as we move inland. This is consistent with findings from Mariotti et al (2020), as they measured an organic matter content of 28±14% in internal brackish marshes compared to 17±7% in salt marshes.…”
Section: Discussionsupporting
confidence: 93%
“…In the inner marshes, organic deposition is more important, indicating that mineral sediment is less available as we move inland. This is consistent with findings from Mariotti et al (2020), as they measured an organic matter content of 28±14% in internal brackish marshes compared to 17±7% in salt marshes.…”
Section: Discussionsupporting
confidence: 93%
“…While this organic contribution can make a difference when relative elevation is optimal for plant growth (Figure 2), even then there is a limit to primary production and, hence, biogenic accretion (Morris et al., 2016). Furthermore, recent work has shown that even in organic‐rich marshes, mud is a key constituent driving vertical accretion (Mariotti et al., 2020).…”
Section: Stratigraphic Coastal Wetland Models and The Role Of Accommomentioning
confidence: 99%
“…Marsh sustainability therefore requires that organic and inorganic sediment accretion keep pace with the compounding impacts of sea level rise and sediment autocompaction (Cahoon et al, 1995). Emergent low marsh can quickly build elevation as marsh grasses increase friction, reduce current velocities, and hasten the trapping of allochthonous suspended sediment (Bouma et al, 2005) and suspended particulate organic material (Mariotti et al, 2020). In addition to trapped sediment, marsh grass growth produces autochthonous vegetative material mainly via its roots, further contributing to marsh platform elevation.…”
Section: Introductionmentioning
confidence: 99%